2021
DOI: 10.1016/s2666-7568(21)00173-2
|View full text |Cite
|
Sign up to set email alerts
|

Computerised cognitive remediation to enhance mobility in older adults: a single-blind, single-centre, randomised trial

Abstract: Background Decline in executive functions and related cognitive processes is associated with mobility decline, and these functions might be amenable to cognitive remediation. This study aimed to examine whether a computerised cognitive remediation programme would improve walking in adults aged 70 years and older.Methods This single-blind, randomised trial at one academic centre in the USA evaluated the efficacy of an 8-week computerised programme (also known as brain games) of progressive intensity and complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…The authors reported an improvement in walking, but this was no greater than in the active control group, who also completed the same amount of CCT but with no progress in the difficulty of the games performed (Verghese et al, 2021 ). Here, the authors report that practice effects might explain the improvements seen in both arms and the lack of between-group differences; however, the investigators also discuss an alternate hypothesis that the more robust effect on executive function tests in the cognitive remediation arm compared to the active control may indicate a true training effect, and raises the possibility that even low levels of cognitive remediation (as in their active control arm) lead to cognitive benefits (Verghese et al, 2021 ). Nevertheless, the current study differed in several ways that might explain the discrepancy in results including, smaller sample size, use of healthy elderly population, wait list control, and the inclusion of neurophysiological measures that were lacking in the previous trial.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The authors reported an improvement in walking, but this was no greater than in the active control group, who also completed the same amount of CCT but with no progress in the difficulty of the games performed (Verghese et al, 2021 ). Here, the authors report that practice effects might explain the improvements seen in both arms and the lack of between-group differences; however, the investigators also discuss an alternate hypothesis that the more robust effect on executive function tests in the cognitive remediation arm compared to the active control may indicate a true training effect, and raises the possibility that even low levels of cognitive remediation (as in their active control arm) lead to cognitive benefits (Verghese et al, 2021 ). Nevertheless, the current study differed in several ways that might explain the discrepancy in results including, smaller sample size, use of healthy elderly population, wait list control, and the inclusion of neurophysiological measures that were lacking in the previous trial.…”
Section: Discussionmentioning
confidence: 98%
“…From the perspective of clinically meaningful change, both gait speeds were increased by more than 0.08 m/s in the intervention group, which was considered a meaningful change in physical performance (Kwon et al, 2009 ). Recently, a larger CCT study of 383 non-demented seniors at high risk for mobility disability was completed (Verghese et al, 2021 ). The authors reported an improvement in walking, but this was no greater than in the active control group, who also completed the same amount of CCT but with no progress in the difficulty of the games performed (Verghese et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations